A educação superior e a pandemia da Covid-19 no Brasil: reflexões sobre a saúde mental entre os universitários - Martins, Tatiane Soares (2024)
This dissertation is part of the line of research Educational Process and Teacher Training of the Master's Program at the Catholic University of Brasília and is part of a larger international research led by the Chair of the United Nations Educational, Scientific and Cultural Organization (Unesco) of Youth, Education and Society, entitled Post-Pandemic Crises Educational Perspectives – PEPPAN. In this sense, this research aims to analyze the perceptions of university students regarding the relationship between mental health and socioeconomic difficulties during the COVID-19 pandemic, its transition and its effects on academic performance. As for the theoretical basis, this study was based on thinkers such as Simmel (2013), Han (2017), Freire (2013), among others. In methodological terms, it had a mixed approach and used the cartographic method. For data collection, questionnaire responses were used, in addition to data generation through interviews. Data from the questionnaires were analyzed using the cartographic method and, in turn, data from the interviews were analyzed using Bardin's content analysis. The students studied are part of bachelor's and undergraduate courses at a higher education institution located in an administrative region of the Federal District. As for the results, we can highlight that the pandemic impacted and demanded more from low-income university students, who were more susceptible to bad weather and emotional turmoil, although we cannot necessarily say, categorically, that they succumbed to them, as this depends on the life story and resilience of each person. In summary, as a social class, young people from the popular classes, as usual, suffered the most impacts. In this context, higher education institutions need to be attentive to the emotional needs of students, particularly by offering assistance from a psychology professional who accompanies them, whether in specific cases or through educational actions. Furthermore, the construction of a welcoming culture must be encouraged, with a view to developing students' socio-emotional skills. In this context, the teacher also needs to be taken care of by the institution, as he is one of the first to observe the weaknesses of students in the classroom.